Magnetism in dilute magnetic oxides and related materials - Gunning, Robert Denis (Trinity College (Dublin, Ireland). School of Physics, 2007)
The work in this thesis is focussed on the magnetic properties of dilute ferromagnetic semiconducting oxides and related materials. Since the first report of unexpected room temperature ferromagnetism in anatase and rutile Co-doped Ti02 in 2001, there has been much research on the magnetic properties of transition-metal doped semiconducting oxides, such as Sn02, ZnO and In2O3 . While many research groups have observed room temperature ferromagnetism in these systems, there is no universal agreement on the origin of the ferromagnetism. Reports of ferromagnetism in HfO2, hexaborides, graphite and sythentic carbon materials have demanded an explanation for the ferromagnetism th at does not involve magnetic cations with a partially filled 3d or 4f electon shells.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin